(untitled) (Research, Society and Development, 2022)
The implementation of emergency remote teaching in the context of the COVID-19 pandemic has had serious impacts on student reality, especially on the psyche of students. Therefore, the present study aimed to analyze the psychological effects of social distancing resulting from COVID-19 in the academic environment. This is an experience report of four students enrolled in various courses at different higher education institutions in Brazil who, through meetings on the Google Meet digital platform, shared their experiences and difficulties on the subject. Among the results found are the prevalence of the feeling of distance, both from teachers and from other colleagues, increasing the feeling of loneliness and the development of mental illnesses such as depression and anxiety. Additionally, another remarkable reality is the internal and external demand to achieve results and expectations, in addition to the positive points arising from this new teaching modality, such as the practicality of displacement and family proximity. It is considered that the current university reality has brought negative and also positive effects for the psychological development of students, both in their academic life and in social interaction.